2003
DOI: 10.1385/abab:109:1-3:263
|View full text |Cite
|
Sign up to set email alerts
|

Production and Energetic Use of Biogas from Energy Crops and Wastes in Germany

Abstract: The production of biogas for reducing fossil CO2 emissions is one of the key strategic issues of the German government and has resulted in the development of new process techniques and new technologies for the energetic use of biogas. Progress has been made in cultivating energy crops for biogas production, in using new reactor systems for anaerobic digestion, and in applying more efficient technologies for combined heat and power production. Recently, integration of fuel cells within the anaerobic digestion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(97 citation statements)
references
References 1 publication
6
88
0
3
Order By: Relevance
“…As Weiland [39], Pöschl et al [40] or Lupp et al [41] point out, responses to climate change warnings can be found in the production of renewable energy by farmers. AD plants fall into the category of facilities for renewable production that should, theoretically, be perceived by the public as less controversial, since they create not only an alternative source of income for farmers (Yiridoe et al [42]) but are also a potential vehicle for rural development (Revelle [43]; Martinat et al [44]; Kostevšek [45]; Warren [46]), by using the waste heat energy released by AD plants for heating local households, farms, etc.…”
Section: Agricultural Ad Plants In Context; Agrarian Change In the Czmentioning
confidence: 99%
“…As Weiland [39], Pöschl et al [40] or Lupp et al [41] point out, responses to climate change warnings can be found in the production of renewable energy by farmers. AD plants fall into the category of facilities for renewable production that should, theoretically, be perceived by the public as less controversial, since they create not only an alternative source of income for farmers (Yiridoe et al [42]) but are also a potential vehicle for rural development (Revelle [43]; Martinat et al [44]; Kostevšek [45]; Warren [46]), by using the waste heat energy released by AD plants for heating local households, farms, etc.…”
Section: Agricultural Ad Plants In Context; Agrarian Change In the Czmentioning
confidence: 99%
“…288 PMD, despite showing similar emissions trend temporally, had a much reduced intensity (up to 56% 289 lower) compared to the BAU. This is mainly attributed to residual CH 4 extraction from post-methantion; 290 reported estimates of residual CH 4 potentials during digestate maturing/long term storage (up to 180 day) 291 vary, ranging from 5-15% to 12-31% of total methane production (Weiland, 2003). These variations are 292 linked to the feed quality, the organic loading rate (OLR) and the HRT of the AD process, as well as the 293 moisture content of the digestate itself, typically reported residual CH 4 potential for animal manure, 294 energy crops and food industry waste range between 2.88 and 37.63 L kg -1 volatile solids (Menardo et al, 295 2011).…”
Section: Methane Emissions 285mentioning
confidence: 99%
“…These research challenges can be alleviated by the production of biogas from biomass sources (plant or organic waste materials) through biological processes (Angelidaki & Ellegaard, 2003). Anaerobic digestion (exposure to oxygen less environment) of plant biomass can be carried out in biogas plants though a series of metabolic processes (Daniels, 1992;Weiland, 2003;Yadvika et. al., 2004).…”
Section: Understanding the Importance Of Biotechnologymentioning
confidence: 99%